2012
DOI: 10.1007/s10389-012-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects of PM10 concentrations on mortality in Tianjin, China: a time-series analysis

Abstract: Aim There are uncertainties regarding the modification effects of season and temperature on the relationship between air pollution and mortality. This study aims to examine the effects of season and temperature on mortality associated with particulate matter less than 10 μm in diameter (PM 10 ) in Tianjin, China. Methods Time-series analysis was used to explore the modification effects of season and temperature on the association between PM 10 and cause-specific mortality in Tianjin between 2006 and 2009. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(43 reference statements)
0
12
3
Order By: Relevance
“…In the case of selecting studies from overlapping datasets, periods or regions, studies with results from more recent and longer periods were selected. In total, eight time-series studies [14-21] and four case-crossover studies [22-25] were finally selected for the meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…In the case of selecting studies from overlapping datasets, periods or regions, studies with results from more recent and longer periods were selected. In total, eight time-series studies [14-21] and four case-crossover studies [22-25] were finally selected for the meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have discussed the effect of the seasonal variation on particle pollutionrelated mortality and morbidity and suggested that higher temperature would significantly enhance the health effects of PM exposure and result in a stronger PM effect on daily mortality (Katsouyanni et al, 1993(Katsouyanni et al, , 2001Ren et al, 2006;Qian et al, 2008). It has been noticed in Beijing (Li et al, 2013b) and Tianjin (Li et al, 2011(Li et al, , 2013a) that adverse effects were strongest in summer compared to the other seasons. The positive association between the higher particle-induced oxidative potential of PM and the higher air temperature may explain why temperature would enhance the PM health effect.…”
Section: Relationship Between the Meteorological Conditions And The Pmentioning
confidence: 99%
“…Severe PM 2.5 pollution in China has attracted considerable public attention [10][11][12] and inspired numerous epidemiological studies to investigate the health effects of air pollution in China since 2013 [13][14][15][16][17][18]. Accurately assessing PM 2.5 exposure is critical for estimating its health risks in such epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately assessing PM 2.5 exposure is critical for estimating its health risks in such epidemiological studies. However, due to the limited number of ground monitors in China, previous studies generally ignored the spatial variation of PM 2.5 and assessed the ambient exposure uniformly using one monitor or averages of several monitors located within a city or a municipality [13][14][15][16], which causes exposure misclassification. Therefore, accurately estimating the fine-scale spatiotemporal variation of ground PM 2.5 may lay a foundation for future health-related studies of PM 2.5 in China.…”
Section: Introductionmentioning
confidence: 99%